O impacto dos novos parâmetros adotados pela ONU para as operações de paz na tradição da política externa brasileira - Paixão, Severino de Ramos Bento da (2008)
The present dissertation analyses the impact of new parameters adopted by The United Nations for peace operations in the tradition of the Brazilian Foreign Policy (BFP). Among the changes occurred in the main foundations that govern such operations, the most important seems to be considerable expansion of the use of force. This growth contradicts the rhetoric and, consequently, the practice of the Brazilian state peaceful conduct concerning international issues, which had become evident by the option of exclusively taking part in Peacekeeping Operations, where the use of force would only be allowed in case of self-defense. The influx of the policy of the government Lula da Silva, aspiring more firmly to be in the United Nations Security Council as a permanent member, causes adjustments in BFP and questions about the possibility to dissociate the power from the responsibility. The Brazilian participation in MINUSTAH, an operation that was already implemented in the new parameters, emerged as an opportunity to achieve this aspiration. However, the retreat by the Government, of the consent to the old rules and attributing it to the new ones, dissociated the practice of the discourse based in the peaceful conduct, modifying the content of both. This inconsistency creates adjustments in the political discourse in order to search for a correction that justifies the new practice allowed by the government. Peace, by consequence, is no longer the aim in itself and it becomes tied to the value of non-indifference. In other words, it gets the notion that the omission facing serious Human Rights violations is a way of avoid the responsibility of the peace existence. This work is an analysis of the process where the peaceful vocation tradition for conflicts solution is reinvented to make a stand against the current demands of foreign policy related to Brazil participation in international collective safety arrangements